Some Biological and Behavioral Studies of the Tetrastichus sp. (Hymenoptera: Eulophidae), a Pupal Parasitoid of Brontispa longissima Gestro (Coleoptera: Chrysomelidae) - Gallego, Vivencio C.; Gallego, Ma. Cynthia E.; Torre, Ivorie J. dela (International Coconut Community, 2013)
The Tetrastichus sp. was identified as a pupal parasitoid indigenous to the Philippines. The total development period of Tetrastichus sp. from egg to adult was 16 days under laboratory conditions. The average incubation, larval and pupal periods were 3.5, 4.8, and 7.4 days, respectively. The average adult longevity was 5.5 (male) and 6.4 (female). Upon emergence of an adult wasp from the host pupa, mating took place shortly and the female look for suitable host pupa of Brontispa longissima for oviposition. Tetrastichus sp. is an endogregarious parasitoid. From one parasitized pupa of Brontispa longissima, around 6 - 66 individual wasps emerged with a mean of 22.4 while parasitized pupae collected from the field yielded 4 - 21 individuals with a mean of 12.7. Majority of the wasps emerged in the morning (70%) while 30% emerged in the afternoon. Sex ratio of male and female was 1:5.4 in laboratory condition while 1:3.7 under field condition with females outnumbered the males. Tetrastichus sp. was observed in some cases to reproduce parthenogenetically. Longevity of Tetrastichus sp. can be enhanced to a mean of 7.3 and 6.0 days by feeding on sugar and honey, respectively while water and coconut pollen resulted in longevity of 3.3 and 2.4 days, respectively. Adults without food lived only one day. Parasitism efficiency ratio of 10 parasitoids: 10 host pupae resulted in 90% parasitism. One to two day old pupa of B. longissima was preferred by Tetrastichus sp. for oviposition with a mean of 86.7% parasitism. Percent pupal parasitism in the field ranged 25.7 - 42.3% with an average of 27.6% in selected areas in Mindanao. Tetrastichus sp. was found to effectively control B. longissima under field condition. The study indicated that Tetrastichus sp. is an effective control agent of B. longissima and could be used in the field to prevent economic damage of the palms by the pest.